HUBUNGAN ANTARA TINGKAT RELIGIUSITAS DENGAN PERILAKU PROSOSIAL PADA MAHASISWA PENGURUS LEMBAGA DAKWAH KAMPUS UNIVERSITAS RIAU - Afri Lizarni; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Religion serves as a guarantor of the actions of the human in achieving a balance and maintaining a social system prevailing in the community by way of organizing all facets of life using the values and norms.This study aims to determine the level of religiosity, level of prosocial behavior and the correlation between the level of religiosity with prosocial behavior on the student board Lembaga Dakwah Kampus Universitas Riau.This research uses a quantitative inferential approach method. As the reference, this study uses Functional theory (AGIL) from Talcott Parson. The population in this research is all students board of the Lembaga Dakwah Kampus Universitas Riau amounted to 1.738 people, then by using table of the sample from Isaac and Michael obtained a magnitude of a sample of 289 people.Sampling technique in this research is proportional random sampling. The results of the research showed that the overall level of religiosity of the respondents is 81% in the high category, 19% in the medium category and 0% in the low category. The level of prosocial behavior of the respondents is 59.9% in the medium category, 40.1% in the high category, and 0% in the low category.The results of the Pearson Product Moment correlation test showed that the value of the correlation coefficient between the variables of religiosity with variable prosocial behavior that is equal to 0.643 with the sig. 0.000 (sig. <0.05), so that the alternative hypothesis (Ha) in this research can be accepted. That means against a strong and positive correlation between level of religiosity with prosocial behavior on the student board Lembaga Dakwah Kampus Universitas Riau. The results of the simple regression values obtained of the coefficient of determination (r-square) is equal 0,413 that influence the level of religiosity toward prosocial behavior on the student board Lembaga Dakwah Kampus Universitas Riau, amounting to 41,3%, while 58,7% influenced by other variables. Keywords: The Correlation, Religiosity, Prosocial Behavior